2003
DOI: 10.1038/nrm1175
|View full text |Cite
|
Sign up to set email alerts
|

Diverse cellular and molecular mechanisms contribute to epithelial plasticity and metastasis

Abstract: In contrast to the aberrant control of proliferation, apoptosis, angiogenesis and lifespan, the cellular mechanisms that cause local invasion and metastasis of tumour cells are still poorly understood. New experimental approaches have identified different types of epithelial-plasticity changes in tumour cells towards fibroblastoid phenotypes as crucial events that occur during metastasis, and many molecules and signalling pathways cooperate to trigger these processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
561
2
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 616 publications
(593 citation statements)
references
References 51 publications
12
561
2
11
Order By: Relevance
“…19 GSEA revealed a significant overlap between the Fra-1-derived gene sets and the genes upregulated in EpRas cells upon TGF-β-induced EMT 21 (Table 1a). Genes associated with c-Myb 29 or with promoters occupied by Smad2/3, 30 two TFs connected to TGF-β and EMT, 31,32 were also enriched (Table 1b) Figure S6a, Figures 5a and b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 GSEA revealed a significant overlap between the Fra-1-derived gene sets and the genes upregulated in EpRas cells upon TGF-β-induced EMT 21 (Table 1a). Genes associated with c-Myb 29 or with promoters occupied by Smad2/3, 30 two TFs connected to TGF-β and EMT, 31,32 were also enriched (Table 1b) Figure S6a, Figures 5a and b).…”
Section: Resultsmentioning
confidence: 99%
“…18 The phenotypic plasticity of this cell line upon Ras/MAPK pathway manipulation has been extensively documented. [19][20][21][22] Expression of c-Fos 18 or cJun 23 in EpH4 cells increases Fra-1 mRNA and promotes EMT. Here we show that ectopic expression of Fra-1 is sufficient to trigger a mesenchymal, invasive and tumorigenic programme in EpH4 cells.…”
mentioning
confidence: 99%
“…In this paper, we described an inducible cellular system (RafER-EpH4) to perform kinetic analysis of EMT, central for both development and tumor progression (Grunert et al, 2003). In this system, MAPK hyperactivation can be induced at will by 4HT activation of the fusion protein dRafER, its strength depending on 4HT concentration.…”
Section: Discussionmentioning
confidence: 99%
“…from benign adenoma to metastatic carcinoma). In particular, the ability of transforming growth factor b (TGFb) to induce EMT has been correlated with a tumor-promoting role of TGFb during late-stage cancer development, contrasted by TGFb-induced cell cycle arrest and apoptosis induced in normal epithelial cells (Derynck et al, 2002;Grunert et al, 2003). Using fully polarized mammary epithelial cells (EpH4) transformed with oncogenic Ras (Ep2Ras), we showed that a Ras-induced hyperactive extracellular signal-regulated kinase (ERK)/ mitogen-activated protein kinase (MAPK) signaling cooperating with TGFb is required to cause EMT in vitro and in vivo and tumor metastasis in nude mice (Oft et al, 1996;Janda et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Extrinsic signals include transforming growth factor beta, hepatocyte growth factor, epidermal growth factor, and fibroblast growth factor overexpression 11, 12, 13, 14. The loss of E‐cadherin is related to a higher risk of metastasis, increased tumor grade, and lower OS 15, 16, 17, 18.…”
Section: Introductionmentioning
confidence: 99%